Community Empowerment from the Perspective of Collaborative Governance in Bojongcae Village and East Kaduagung Village, Lebak Regency - Wiyatama, Afika Rinda; Syawalia, Mutiara; Kurniawati, Nila (KnE Social Sciences, 2025)
Village independence status and the achievement of SDGs are related to community empowerment in Bojongcae Village and East Kaduagung Village, Lebak Regency. These villages have different statuses of village independence. Bojongcae Village is classified as an underdeveloped village, while East Kaduagung Village is categorized as developed village. Collaborative governance is crucial for building community development through empowerment. With collaborative governance, the government can work together with the community to address and provide solutions through various actors from both government and non-government sectors, ensuring that the benefits of such commitments are experienced by all parties involved. This study aims to analyze community empowerment in Bojongcae Village and East Kaduagung Village based on the five collaborative indicators of Ansell & Gash. The research method used is descriptive qualitative with a case study approach. The results indicate that community empowerment in Bojongcae Village and East Kaduagung Village is carried out solely with the involvement of the government and the community. Furthermore, based on the collaborative indicators of Ansell & Gash, it is apparent that all indicators are not yet optimal for achieving collaborative governance in these villages due to the lack of specific empowerment programs from the village government for the community caused by budget constraints, gaps in understanding, and limited collaboration only between the government and the community. Therefore, there is a need for the expansion of collaboration in community empowerment efforts.